Poststroke survival for black-Caribbean populations in barbados and South london - Wolfe, Charles D A; Corbin, David O C; Smeeton, Nigel C; Gay, Glenda H E; Rudd, Anthony G; Hennis, Anselm J; Wilks, Rainford J; Fraser, Henry S (Stroke (1970), 2006)
There are variations in mortality rates for stroke in black communities, but the factors associated with survival remain unclear. The authors studied population-based stroke registers with follow up in South London (270 participants, 1995 to 2002) and Barbados (578 participants, 2001 to 2003). Differences in sociodemographic factors, stroke risk factors and their management, case severity, and acute management between London and Barbados were studied. Survival analysis used Kaplan-Meier curves, log-rank test, and Cox proportional hazards model with stratification. There were 1411 person-years of follow-up. Patients in Barbados had poorer survival (log-rank test P=0.037), particularly those with a prestroke Barthel index scores between 15 and 20 (1-year survival, 56.4% versus 74.3%; P<0.001). This disadvantage remained significant (hazard ratio [HR], 1.99; 95% CI, 1.23 to 3.21, P=0.005) after adjustment for age and year of stroke and stratification for stroke subtype and socioeconomic status (SES). After stratification by SES, clinical stroke subtype, and Glasgow Coma Score, and adjustment for other potential confounders, additional factors reducing survival were untreated atrial fibrillation (AF; HR, 8.54; 95% CI, 2.14 to 34.08, P=0.002), incontinence after stroke (HR, 2.64; 95% CI, 1.79 to 3.89), and dysphagia (HR, 2.25; 95% CI, 1.57 to 3.24). Patients not admitted to the hospital had improved survival (HR, 0.35; 95% CI, 0.21 to 0.58). Interaction terms between location and Barthel score, location and AF, and location and transient ischemic attack were included in the final model to reflect the greater difference in survival with a high Barthel score of 15 or more, absence of untreated AF, and having untreated transient ischemic attack. Black-Caribbean people with stroke living in Barbados have worse survival than similar patients in South London, particularly if they have good mobility before the stroke. Further exploration and refinement of measurement of confounding factors such as SES and poststroke management along with exploring the cultural/environmental differences between the communities is required to understand these stark differences.